The Effect of the Outdoor Study Method on Elementary School Students' Science Learning Outcomes - Suratman Suratman; Mukhtar Mukhtar; Nurahmania Nurahmania; Mulya Yusnarti; Ilham Ilham (Jurnal Evaluasi dan Kajian Strategis Pendidikan Dasar, 2026)
Elementary IPAS learning requires concrete and contextual experiences, yet classroom practice often remains dominated by teacher explanation and textbook-based activities. This study aimed to examine the effect of the Outdoor Study method on elementary students’ IPAS learning outcomes. A quantitative approach with a quasi-experimental nonequivalent control group design was used. The participants were 36 fourth-grade students, consisting of 18 students in the experimental group and 18 students in the control group. The experimental group learned through Outdoor Study activities involving environmental observation, exploration, discussion, presentation, and reflection, while the control group received conventional classroom instruction. Data were collected using IPAS learning outcome tests and analyzed through descriptive statistics, normality and homogeneity tests, and an independent samples t-test. The results showed that the experimental group achieved a higher posttest mean score (M = 85.75) than the control group (M = 78.50). The difference was statistically significant, t = 3.214, p = .001. These findings indicate that Outdoor Study positively affects IPAS learning outcomes by providing concrete experiences and encouraging active student participation.